Drug‐Induced Renal Vasculitis: Etiology, Pathogenesis, Clinical Manifestations, and Therapeutic Approaches—A Narrative Review - Hashim Mohamed Siraj; Masab Ali; Sampda Sanjaykumar Sharma; Afreen Begum; Muhammad Husnain Ahmad; Muhammad Hassan; Roba Kamaleldin Moustafa Kamel Aref Elsayed; Muhammad Hamza Tahir (Health Science Reports)
ABSTRACT Background and Aims Drug‐induced renal vasculitis arises from various medications that cause immunological dysregulation or direct vascular damage, leading to inflammation and thrombosis. Clinical manifestations vary widely, from mild constitutional symptoms to severe organ dysfunction. This review aims to thoroughly explore drug‐induced renal vasculitis, focusing on its etiology, pathological mechanisms, clinical manifestations, diagnostic challenges, and therapeutic approaches. This review aims to summarize current knowledge and highlight areas requiring further research. Methods A comprehensive literature search was conducted using PubMed, MEDLINE, Embase, and Cochrane Library databases. We included peer‐reviewed journal articles and excluded those with insufficient data, poor quality, or lack of relevance. The search terms included combinations of “renal vasculitis,” “drug‐induced vasculitis,” “drug‐related nephritis,” “medication‐induced renal vasculitis,” and specific drug names. An initial search yielded 13,192 articles, of which 13,103 were excluded due to irrelevance, duplication, or outdated information. After full‐text review, 99 peer‐reviewed articles were included. Results Discontinuation of the offending drug is the primary and most crucial step in managing drug‐induced renal vasculitis. Prognosis is generally more favorable than primary vasculitis, with a high remission rate if the offending drug is stopped early. Due to its rarity, epidemiological data is limited. Diagnosis frequently relies on autoantibodies [antineutrophil cytoplasm antibodies (ANCA), myeloperoxidase (MPO), antinuclear antibody (ANA)] and clinical symptoms, with renal biopsy confirming it. Factors such as high‐dose and long‐term drug use, as well as genetic predispositions, increase the risk. Conclusion This review provides a comprehensive overview of drug‐induced renal vasculitis, discussing what is known and identifying gaps in understanding. While discontinuing the causative drug remains the cornerstone of management, further research is needed, particularly in developing a formal tool to assess the quality of studies and minimize selection bias.